(untitled) (Applied Biological Research, 2020)
A two-year field experiment was conducted during rabi seasons of 2016-17 and 2017-18 at Agricultural Farm of Palli Siksha Bhavana, Visva-Bharati, Sriniketan, West Bengal (India) to assess the effects of herbicide mixtures on weed population, weed biomass, weed control efficiency, weed index, crop dry weight and grain yield in wheat crop. Eight herbicide treatments along with weed-free and weedy check were evaluated in a completely randomized block design with three replications. Post-emergence application of sulfosulfuron (25 g ha-1) + metsulfuron methyl (2 g ha-1) 30 days after seed sowing proved very effective against broad-leaved weeds and annual grasses. The above treatment recorded significantly lower density and biomass of weeds as compared to all other treatments. After weed-free plot, maximum crop dry weight (514.35 g m-2) and highest grain yield (3.03 t ha-1) were obtained from sulfosulfuron + metsulfuron methyl (25 g a.i ha 1+ 2 g a.i ha-1) treated plot. All other herbicide mixtures tested also proved very effective in controlling the weeds and increased wheat yield significantly. The herbicide mixtures could be helpful to prevent or delay the development of herbicide resistance in weeds and thus may reduceherbicide residues in soil.